Análise da influência do modal aéreo no desenvolvimento regional do oeste paranaense - Tscha, Olga da Conceição Pinto (2010)
The west region of the state of Parana, although having a significant transportation infrastructure, capable of supporting the important route of national and international tourism, presents little diversification in passenger transportation. This way, investments in infrastructure, location and influence area that the airport of Cascavel has on the region could determine the choice of this mode of transportation by users of the west region of Parana as means of transportation. The objective is to analyze the influence measured in distance between the cities and check what is the probability of the cities of the west region of Parana of using air transport for their displacements; verification to be done by application of Huff s gravity model. For that, the options of destinations of the airports of Cascavel, Foz do Iguaçu and Maringá were used. The results show that, in the current situation, that is, with 34 options of destination, the airport of Cascavel has little influence on the region s users of air transport. In a hypothesis, however, that the three airports analyzed have the same number of destinations, that is, 202, the airport with the biggest capability of growth and development is the one of Cascavel. This fact may be justified by its geographical position in the west region of Parana.